2018
DOI: 10.3390/d10030053
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antioxidant Potential Differences between Cynomorium coccineum L. Growing in Italy and in Tunisia: Effect of Environmental Stress

Abstract: Cynomorium coccineum is a parasitic plant that has been known for centuries in ethnopharmacology. However, its biological activities have been scarcely studied, particularly in the case of plant grown in North Africa. Thus, we compared the chemical composition and antioxidant potential of C. coccineum taken from two regions characterized by very different climates: the Tataouine region in southeast Tunisia, which lies near the desert, and Sardinia in south Italy, which lies near the coast. The antioxidant pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Our study showed that Cynomorium possessed even stronger anticancer activity. Recently, it was shown that the water extract of C. coccineum possesses antioxidant activities [ 36 ]. In addition, different components from this species also exert antimicrobial and antityrosinase activities [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our study showed that Cynomorium possessed even stronger anticancer activity. Recently, it was shown that the water extract of C. coccineum possesses antioxidant activities [ 36 ]. In addition, different components from this species also exert antimicrobial and antityrosinase activities [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a series of papers, the lipid profile of Sardinian C. coccineum Supercritical Fluid Extract (SFE) oil has been elucidated [34], showing an almost 1:1:1 concentration of saturated fatty acids (SFA, mainly palmitic acid 16:0 and stearic acid 18:0), monounsaturated fatty acids (MUFA, mainly oleic acid 18:1 n-9), and polyunsaturated fatty acids (PUFA) [28,37]. The same authors confirmed this pattern in a Tunisian sample [33], suggesting a promising nutraceutical source of functional and beneficial compounds (for example, about 11% of the SFE oils was 18:3 n-3). However, different accessions (also from the same geographical area) showed a high variability not only in the total quantity, but also in the oil composition [28,34], probably due to different annual weather fluctuations or small differences in the collection/extraction procedures.…”
Section: Phytochemistrymentioning
confidence: 90%
“…In a recent work, Ben Attia et al (2018) compared the chemical compositions of C. coccineum plants from Sardinia and Tunisia, describing a differential chemical profile, possibly due to the climatic conditions (more arid in the Tunisian desert, and temperate in the Mediterranean basin). The phenolics, in fact, were differently distributed among solvents at various polarities [33]. Additionally, these authors used 1 H-NMR to identify several amino acids (including proline, glutamine, valine, threonine, alanine, and asparagine) and mono-, bi-, and tricarboxylic organic acids (i.e., acetate, formate, and several common intermediates of biochemical pathways such as citrate, fumarate, malate, malonate, and succinate) in Sardinian and Tunisian samples.…”
Section: Phytochemistrymentioning
confidence: 99%
“…The reported IC50 was similar to rutin, chosen as the standard. Unfortunately, to our knowledge, no antioxidant activity has been determined for SO extracts using commonly electron-transfer or hydrogen atom-transfer assays [21].…”
Section: Antioxidant Activitymentioning
confidence: 99%